2018
DOI: 10.5007/1980-0037.2018v20n4p532
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity of parents and of their children: a systematic review of Brazilian sample studies – Report Card Brazil

Abstract: The aim of this study was systematically review the researches in regard the association of PA of parents and the PA of their children. A literature search was performed in five databases (Medline, Embase, Cinahl, Lilacs and SciELO) using combined terms about youth, PA and social support, with restriction to publications with Brazilian sample and to English and Portuguese language. Thirteen studies were included in this review and was observed a positive association of parental PA and the PA of their children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
2
3
1
1
Order By: Relevance
“…To conclude, parents play an important role in promoting their children's active lifestyles. Although compared with other studies [30,33,54], the results are not always consistent, the present study suggested a strong relationship between the SC of parents and SC of children younger than eight years, the strongest being the relationship between mothers and daughters aged 4-7.9 years, especially at weekends. At a later age, the parent-child association is more affected by gender-based differences, with a dominant association especially between fathers and sons.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…To conclude, parents play an important role in promoting their children's active lifestyles. Although compared with other studies [30,33,54], the results are not always consistent, the present study suggested a strong relationship between the SC of parents and SC of children younger than eight years, the strongest being the relationship between mothers and daughters aged 4-7.9 years, especially at weekends. At a later age, the parent-child association is more affected by gender-based differences, with a dominant association especially between fathers and sons.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study also confirmed a gender-specific parent-child SC relationship, which is consistent with a Brazilian study on parent-child associations [33]. Some studies also reported different results concerning parent-child PA associations with respect to the children's or parents' gender [30,33,54].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consequentemente, conhece os benefícios da prática regular da AF em relação à saúde e a qualidade de vida [1][2][3]5 . Devido a isso, todos os esforços no sentido de combater a inatividade física são válidos, dentre eles destacam-se as políticas públicas 11 , as mudanças nos hábitos diários 8,9 e o envolvimento em atividades comunitárias 20 e familiares 21 .…”
Section: /unclassified